Improvement of Language Understanding using Sentence Identification Methods in Mathematics Subject of Story Matter in 4th Grade MI - Lilik Minarni (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
This aims of study is to improve the understanding of language by identifying the main sentence in mathematics subject especially in the story matter. The methods of this research is class room action reseach by doing two cycles proccess.  The collecting data method was obtained by observation, test, and documentation.  Data analysis proccess was done by using an interactive model consisting of four components of analysis including data colection, selection, presentation, and conclusion.Based on the results, sentences identification learning method can be increased language understanding to solve the problem of story matter in mathematic subject in 4th grade in MI. Thus, it could be concluded that in mathematics learning by using sentences identification methods can be used to increase MI student ability to solve the story of matter. By the methods, the students will be easy to understand the sentences, so thet can finish and solve the test, and also they can made their sentences on their mind.